East Asia in the Aftermath : Was there a Crunch? - Ghosh, Atish (IMF Working Papers; Working Paper ;, 1999)
This paper uses a disequilibrium framework to investigate a possible credit crunch in the East Asian crisis countries (Indonesia, Korea, and Thailand) during 1997-98. It defines a credit crunch as a situation in which interest rates do not equilibrate supply and demand for credit and the aggregate amount is supply constrained, id est there is quantity rationing. In all three countries, rising real interest rates and weakening economic activity lowered credit demand and (with the exception of Indonesia in late 1997) there is little evidence of quantity rationing at the aggregate level-although individual firms may have lost access to credit.